2010
DOI: 10.1007/s00595-009-4269-1
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic gastric mucosa in the gallbladder: Report of two cases

Abstract: This report presents two cases of heterotopic gastric mucosa in the gallbladder. In case 1, the patient was a 43-year-old man who presented with diarrhea and fever. Abdominal ultrasonography showed a sessile polypoid lesion in the body of the gallbladder that grew over 2 months. Gallbladder carcinoma was suspected and a cholecystectomy was performed. Examination of an intraoperative frozen specimen of the elevated lesion in the body of the gallbladder suggested a gallbladder carcinoma invading the subserosal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Gastric heterotopia in the gall bladder may be asymptomatic or in the form of pain in the right hypochondrium radiating to the right shoulder, as in our patient's case [11]. Previously, findings regarding serological parameters have been rarely described in the literature [12].…”
Section: Discussionmentioning
confidence: 62%
“…Gastric heterotopia in the gall bladder may be asymptomatic or in the form of pain in the right hypochondrium radiating to the right shoulder, as in our patient's case [11]. Previously, findings regarding serological parameters have been rarely described in the literature [12].…”
Section: Discussionmentioning
confidence: 62%
“…Some authors described a predominantly incidental discovery of heterotopic gastric mucosa. [ 8 ] However, our analysis showed that 74.3% of the patients were symptomatic. Yet, this finding might be influenced by a possible publication bias.…”
Section: Discussionmentioning
confidence: 76%
“…[ 7 ] Clinically, HMG is often asymptomatic and is most often an incidental finding. [ 8 ] On the other side, it can also become symptomatic and can even present as an acute abdomen with possible hazardous perforation. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Since the first description by Ewell and Jackson in 1939, GH has been described throughout the GI tract, pancreatobiliary tract, nasopharynx and several unusual locations, such as the mediastinum and scrotum . Although the exact pathogenesis remains largely unresolved, several hypotheses have been put forward to explain the occurrence of heterotopic gastric mucosa in the GI tract.…”
Section: Discussionmentioning
confidence: 99%